The impact of implementing and sustaining the international guidelines for skin-to-skin contact in the first hour after birth in Uganda - Kajsa Brimdyr; Scovia Nalugo Mbalinda; Anna Blair; Kristin Svensson; Mike Kagawa; Melissa Reyes; Louise Racine Bastarache; Livingstone Kamoga; Edwin Kigozi; Karin Cadwell (Scientific Reports)
Abstract Skin-to-skin contact between the mother and baby during the first hour after birth has significant benefits for mother, newborn and breastfeeding. However, optimal implementation is highly variable. The 2023 International Guidelines on skin-to-skin contact in the first hour after birth place high confidence in the evidence that immediate, continuous, uninterrupted skin-to-skin contact should be routine for all mothers and all babies over 1000 g, regardless of mode of delivery. The PRECESS (Practice Reflection Education and Training Combined with Ethnography for Sustainable Success) methodology provides evidence-based education, process-oriented practice, experiential learning and Interactive Analysis Labs to achieve sustainable best practice. This study aimed to determine if, using PRECESS methodology, the 2023 guideline could be fully implemented and sustained in a regional teaching and referral hospital in Uganda, and whether this resulted in an increase of breastfeeding initiation in the first hour after birth. PRECESS is a prospective cohort study methodology. Baseline data on a convenience sample of 92 dyads was collected, and video recordings made, of each newborn during the first hour after birth. Then, intervention began with an evidence-based lecture for health care workers describing the optimal practice of skin-to-skin contact and first-hour newborn behaviors. Practice experience followed the lecture with all of the health care workers as they came on shift for 105 dyads, who were also video recorded for the first hour. Interactive Analysis Labs allowed key informants to provide reflection on barriers and solutions. Approximately 6 weeks after the initial intervention, 128 dyads were observed and video recorded to determine sustainability of the procedure. Implementation of skin-to-skin contact in the first hour after birth using PRECESS resulted in significantly more time in skin-to-skin contact than pre-intervention (2 m 25 s + − 2 m 48 s vs. 57 m 51 s + −2 m 53 s p < 0.001), although breastfeeding rates in the first hour after birth were not significantly different (29% in baseline, 28% after intervention, p = 0.871). After 6 weeks, skin-to-skin contact in the first hour after birth remained high, at 58 m 17 s + − 2 m 02 s. Breastfeeding in the first hour after birth increased to 44% (p = 0.012). PRECESS provided a fast-track methodology for improving skin-to-skin contact and breastfeeding in the first hour after birth in a regional teaching and referral hospital in Uganda.